DETERMINATION FACTORS OF UNEMPLOYMENT IN BANTEN - Anggreny Yuseva Pardosi; Septriani Septriani (SEAN Institute, 2023)
The aim of this research is to determine the influence of HDI, Poverty, Minimum Wage on Unemployment in Banten 2017-2022. This research uses quantitative methods and the type of data used is panel data which is a combination of time series data from 2017-2022 and cross sections of 29 districts/cities. The data analysis sprocess uses panel data regression analysis using the best model, namely the Common Effect Model (CEM) which is processed using the Eviews 13 program. It can be concluded that the HDI variable has a significant negative effect on Unemployment, Poverty and Minimum Wage has a significant effect on Unemployment in the District/ Banten City during 2017-2022. It would be best to overcome the unemployment problem in Banten, the Banten Provincial Government is expected to pay more attention to human development. Through increasing human development, it is hoped that human quality will improve and ultimately reduce the high level of unemployment. To the government, statistical data should be used by the Banten Provincial Government, district government and city government through Bappeda in every program planning so that poverty management can be integrated, no ineffective activities should be combined to reduce the poverty rate. Apart from that, the Banten provincial government can make adjustments to the minimum wage.